Exploring the Classic and Novel Pathogenetic Insights of Plastic Exposure in the Genesis and Progression of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) - Mario Romeo; Marcello Dallio; Fiammetta Di Nardo; Giuseppina Martinelli; Claudio Basile; Alessia Silvestrin; Giusy Senese; Annachiara Coppola; Carmine Napolitano; Angela Amoresano; Carlo Altucci; Alessandro Federico (Livers)
The term “plastics” is an umbrella term generally referring to any material containing a high level of polymer content as an essential ingredient. Micro(nano)plastics (MNPs) are derived from the degradation of plastics, representing exogenous substances whose exposure can potentially interfere with different physiological processes. In this scenario, even considering the relative paramount detoxification role, the liver emerges as a key active organ in the relationship between plastic exposure and human disease. In industrialized countries, where plastics constitute largely diffused components of objects routinely adopted in daily/social life, including food packaging, Metabolic dysfunction-associated Steatotic Liver Disease (MASLD) represents the predominant hepatopathy and is progressively becoming the leading cause of cirrhosis and liver cancer, with an incompletely elucidated multifactorial pathogenesis. Notably, oral exposure to MNPs has been revealed to impact the gut–liver axis by influencing gut microbiota composition, gastrointestinal absorption, and, ultimately, determining hepatic accumulation. At the hepatic level, MNPs can contribute to the onset and worsening of steatosis by inducing metabolic dysfunction and inflammation. Plastics can also serve as vectors for different potentially toxic additives, with specific MNPs constituting a persistent source of release of bisphenol A (BPA), a well-recognized exogenous etiological factor contributing to MASLD genesis and worsening. Recently, exposure to MNPs and additives has demonstrated significant impacts on the immune system, oxidative stress, and metabolism. In particular, polystyrene-derived MNPs impair the mechanisms regulating hepatic lipid metabolism, simultaneously acting as antigens abnormally triggering the innate immune response. At the same time, environmental BPA exposure has been revealed to trigger trained immunity-related pathways, configuring novel pathogenetic drivers potentially promoting the progression of MASLD. The present review, after rapidly overviewing the main sources and toxicological properties of MNPs and related additives, explores plastic-related exposure’s potential implications in the genesis and progression of hepatic steatosis, highlighting the urgent need for further clarification of relative pathogenetic mechanisms.